2020
DOI: 10.1371/journal.pone.0238549
|View full text |Cite
|
Sign up to set email alerts
|

Comparative iTRAQ proteomic profiling of proteins associated with the adaptation of brown planthopper to moderately resistant vs. susceptible rice varieties

Abstract: The brown planthopper (BPH), Nilaparvata lugens (Stål), is a destructive pest that poses a significant threat to rice plants worldwide. To explore how BPHs adapt to the resistant rice variety, we analyzed proteomics profiles of two virulent N. lugens populations. We focused on Biotype Y, which can survive on the moderately resistant rice variety YHY15, and Biotype I, which can survive on the susceptible rice variety TN1. We performed protein quantitation using the isobaric tag for relative and absolute quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Global studies of proteins and metabolites are usually combined with transcription profiling (Table 1 and Table 2). In general, the fluctuation of major molecules is well corelated with gene expression (Sana et al 2010;Zha and You 2020); however, inconsistencies have also been observed. Peroxidase expression is not associated with the activity between Nipponbare and O. meyeriana (Chen et al 2016).…”
Section: Consistency In Global Studies Of Transcripts and Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global studies of proteins and metabolites are usually combined with transcription profiling (Table 1 and Table 2). In general, the fluctuation of major molecules is well corelated with gene expression (Sana et al 2010;Zha and You 2020); however, inconsistencies have also been observed. Peroxidase expression is not associated with the activity between Nipponbare and O. meyeriana (Chen et al 2016).…”
Section: Consistency In Global Studies Of Transcripts and Proteinsmentioning
confidence: 99%
“…Proteomics and metabolomics studies on rice response to BPH infection have revealed the occurrence of dynamic changes. Lipid transport and metabolism, SM biosynthesis, amino acid transport and metabolism, and phytohormone signaling are commonly induced by BPH in both susceptible and resistant cultivars (Wei et al 2009 ; Dong et al 2017 ; Zhang et al 2018 ; Zhang et al 2019 ; Zha and You 2020 ). Notably, studies that have utilized resistant and susceptible cultivars to observe changes on protein and metabolite levels have identified markers and features associated with resistance to BPH infection.…”
Section: Response Of Rice To Various Biotic Stresses Considering Protmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the molecular mechanism of BPH adaptation to resistant rice variety. In our previous study, proteomic profiles and miRNA expression profiles of BPH were analyzed ( Zha & You, 2020 ; Zha et al, 2016 ). In these studies, there has been evidence that miRNA may be involved in the co-evolution process of rice planthopper resistance, and proteome analysis also found many differentially expressed proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the molecular mechanism of co-evolution between BPH and resistant rice, in our previous report, proteomics and miRNA sequencing were performed using a susceptible rice variety (TN1) as a control and a moderately resistant rice variety (YHY15) carrying the resistance gene BPH15 ( Zha & You, 2020 ; Zha et al, 2016 ). However, the molecular mechanism and regulatory network are still unclear.…”
Section: Introductionmentioning
confidence: 99%